2017
DOI: 10.1039/c7cc06967g
|View full text |Cite
|
Sign up to set email alerts
|

Design of encapsulated hosts and guests for highly efficient blue and green thermally activated delayed fluorescence OLEDs based on a solution-process

Abstract: The molecular aggregation and exciton-polaron interaction of the host-guest system were successfully restricted by efficient molecular encapsulation. The solution-processed blue and green TADF OLEDs have been realized with external quantum efficiencies above 23% by employing the encapsulated TADF host and guest as emission layers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 33 publications
0
15
0
1
Order By: Relevance
“…The peripheral carbazole dendrons can suppress both the molecular aggregation and triplet‐polaron quenching (TPQ) effect. Based on these dendritic emitters, solution‐processed blue and green TADF OLED devices with the structure ITO/PEDOT:PSS (40 nm)/(Cz‐3CzCN:Cz‐CzCN or Cz‐3CzBN:Cz‐4CzBN) (60 nm)/TPBi (40 nm)/Cs 2 CO 3 (2 nm)/Al and with maximum EQEs of 23.5% and 23.8%, respectively, have been prepared, some of the highest values reported so far for any solution‐processed OLED devices …”
Section: Tadf Polymersmentioning
confidence: 99%
“…The peripheral carbazole dendrons can suppress both the molecular aggregation and triplet‐polaron quenching (TPQ) effect. Based on these dendritic emitters, solution‐processed blue and green TADF OLED devices with the structure ITO/PEDOT:PSS (40 nm)/(Cz‐3CzCN:Cz‐CzCN or Cz‐3CzBN:Cz‐4CzBN) (60 nm)/TPBi (40 nm)/Cs 2 CO 3 (2 nm)/Al and with maximum EQEs of 23.5% and 23.8%, respectively, have been prepared, some of the highest values reported so far for any solution‐processed OLED devices …”
Section: Tadf Polymersmentioning
confidence: 99%
“…An efficient and simple D-A approach to achieve white light from organic solids with a polymorph dependent TADF property has been developed by Ban et al ( 2017 ). A purely organic molecule of 3-(diphenylamino)-9H-xanthen-9-one (3-DPH-XO) has been reported, which was found to display bright white light emission with the CIE value (0.27, 0.35) in its solid state, facilitated by spontaneous formation of polymorphs with distinguished intermolecular non-covalent interaction features that determined the different emission colors, and which was further demonstrated by single crystal studies of the compound (shown in Figure 17 ).…”
Section: Recent Progress On Multi-functional Tadf Emittersmentioning
confidence: 99%
“…Moreover, an ever-increasing demand to use them as a solution-processed non-doped fabrication technique gives them an extra edge over other existing methods for solid-state lighting. However, the major issues of efficiency improvement affected by emission quenching in non-doped thin-film state is mainly due to singlet-triplet annihilation (STA), long lifetime triplet-polaron, and triplet-triplet annihilation (TTA) (Ban et al, 2017 ). Yet, quenching the effect of TADF emitters can be fixed by co-existing with an impressive solid state emission property, called aggregation induced emission (AIE), a condensed state emission behavior that can arrest the rotation or vibration in a highly twisted molecular configuration likewise TADF molecular structure.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the independent energy and charge transfer channels of nonconjugated molecular configuration in this type of TADF dendrimers, the dendrimer‐based EL devices were also investigated by using Cz‐3CzCN as the host and Cz‐4CzCN being guest, aiming at suppressing of the triplet‐polaron quenching (TPQ) effect of both the host and guest materials without sacrificing their TADF feature . The transient PL spectrum of Cz‐3CzCN:Cz‐4CzCN exhibited more delayed component than the parent 3CzCN:4CzCN, indicating that the dendritic structure could suppress triplet–triplet annihilation (TTA) process.…”
Section: Tadf Dendrimersmentioning
confidence: 99%